Experience of healthcare discrimination reported by individuals with a history of gynecologic cancer in the All of Us research program - Allison C. Dona; Patricia I. Jewett; Sarah Davidson; Deanna Teoh; Rachel I. Vogel (Gynecologic Oncology Reports)
Objective: We aimed to describe prevalence of healthcare discrimination in All of Us participants with a history of gynecologic cancer and compare patient experiences of discrimination by gynecologic cancer type. Methods: We analyzed survey data of participants with a history of gynecologic cancer in the All of Us Research Program. Cancer status was defined using self-report or electronic health record documentation. Healthcare discrimination was measured by the Discrimination in Medical Settings (DMS) Scale. Potential confounders were self-reported (cigarette use, sexual orientation, gender, race, ethnicity, income, education, and age) and physical measurement (body mass index). We report associations between gynecologic cancer site (cervical, ovarian, uterine, vaginal or vulvar, more than one) and DMS scores using multivariable logistic regression. Results: Of 2,195 participants, 1,001 had cervical, 579 uterine, 419 ovarian, 30 vaginal/vulvar, and 166 more than one gynecologic cancer. Most (76.5%) reported experiencing any healthcare discrimination, and 45.0% reported frequent healthcare discrimination. Those with a history of cervical cancer (52%, OR: 1.80, 95% CI: 1.42, 2.28) and multiple cancers (47.8%, OR: 1.53, 95% CI: 1.05, 2.21) had higher odds of frequently reporting discrimination than those with a history of ovarian cancer (37.5%) in the unadjusted model. The relationship observed remained but was attenuated in the adjusted model (Cervical OR: 1.35, 95% CI: 1.04, 1.75; Multiple OR: 1.35 95% CI: 0.91, 2.00). Conclusions: Healthcare discrimination was reported across cancer types. Individuals with a history of cervical or multiple gynecologic malignancies reported frequent healthcare discrimination more often than those with other gynecologic cancers.